2023
DOI: 10.1097/bsd.0000000000001431
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Posterior Atlantoaxial Dislocation With an Associated Fracture

Abstract: Study design: Systematic review. Objective: To investigate the clinical presentation, mechanism of injury, patients’ characteristics, diagnosis, treatment, and prognosis of traumatic posterior atlantoaxial dislocation with fracture (TPAD). Background: TPAD is an extremely rare entity, with a limited number of cases reported in the literature. Although rare, a thorough understanding of the pathogenesis and management of such cases is required due to the high risk of spinal cord compression and the severity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Posterior instability occurs when the integrity of the bony support, either the odontoid process or the anterior arch of C1 is compromised by major trauma, leading to posterior displacement of C1 in relation to C2. 2 Regarding the treatment of atlantoaxial dislocation, there is a consensus that reduction has to be performed as soon as possible in all cases, to prevent residual instability and development of permanent deformity. Several authors reported that the reduction of the dislocation was achieved using traction but all cases were atlantoaxial dislocation with an isolated odontoid process fracture (without C1 fracture).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Posterior instability occurs when the integrity of the bony support, either the odontoid process or the anterior arch of C1 is compromised by major trauma, leading to posterior displacement of C1 in relation to C2. 2 Regarding the treatment of atlantoaxial dislocation, there is a consensus that reduction has to be performed as soon as possible in all cases, to prevent residual instability and development of permanent deformity. Several authors reported that the reduction of the dislocation was achieved using traction but all cases were atlantoaxial dislocation with an isolated odontoid process fracture (without C1 fracture).…”
Section: Discussionmentioning
confidence: 99%
“…The odontoid process acts as a pivoting anchor in the C1–C2 configuration, which makes the trans‐odontoid luxation fracture a highly unstable traumatic lesion of the atlantoaxial complex. Posterior instability occurs when the integrity of the bony support, either the odontoid process or the anterior arch of C1 is compromised by major trauma, leading to posterior displacement of C1 in relation to C2 2 . Regarding the treatment of atlantoaxial dislocation, there is a consensus that reduction has to be performed as soon as possible in all cases, to prevent residual instability and development of permanent deformity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations